Taste Masking Cetirizine Hydrochloride using Ion-exchange Resins - Sridhar, Vanga; Thirupathi, Kaluvala; Sridhar, Mittapally (Current Indian Science, 2023)
AimThe scope of the study is to determine the exact drug content present in the dry resinate and the utilization of ion-exchange resin in taste masking highly bitter cetirizine hydrochloride (CTZ). The Amberlite® IRP-69 cross-linked polystyrene was used.ObjectiveThe objectives of this study are drug loading, drug–resin ratios, effect of particle size determination, and qualitative evaluation of taste masking ion-exchange resins.BackgroundThe resinate (drug–resin complex) preparation process was completed by batch method in the ratio of 1:1, 1:2, and 1:3. The loaded drug amount in the resin was evaluated spectrophotometrically by measuring the remaining drug to be loaded in the solution at 278nm. Different sieve sizes of Amberlite® IRP-69 resins were employed to determine the effect of the particle size in drug loading and drug releasing profiles in simulated gastric fluid without enzymes. The X-ray diffractograms of cetirizine hydrochloride, Amberlite® IRP-69, and a mixture of cetirizine hydrochloride with resins (resinate) were obtained by using an X-ray diffractometer.ResultsResinates were developed by using single-batch and double-batch methods. Both of them are giving almost the same results of drug loading into ion-exchange resins. We selected 1:1 drug–resin ratio to see the effect of the particle size on the rate and extent of drug loading and drug releasing from the complex. In the 1:1 drug-to-resin ratio, almost 78% of the drug was involved in the complex after 24 hours; in the case of 2:1 and 3:1 ratios, only 49% and 25% of the drug were involved in the complex, respectively.ConclusionAmong many taste masking methods, the formation of resinates with an ion-exchange resin is simple and inexpensive. The present work reveals that the degree of bitterness of cetirizine hydrochloride is reduced to zero by strong cation-exchange resin. The present study deals on the scope of utilizing ion-exchange resins in taste masking cetirizine hydrochloride (CTZ), a highly bitter drug.
Keywords: Cetirizine Hydrochloride